Future of individuals after out-of-home care - Lára Björg Grétarsdóttir 1988- (2018)
Various studies have described life outcomes for individuals that go through diverse forms of out-of-home care. Individuals who have been placed in out-of-home care are at great risk of developing mental health problems, low self-esteem and low resilience, and estimating their quality of life poor and are likely to have a bleaker future outcome. No studies have assessed the emotional well-being, self-esteem, quality of life, resilience and life satisfaction of individuals who have been in out-of-home care in Iceland. The purpose of the study is to shed a light on the well-being of Icelandic adults who were placed in out-of-home care in childhood and to gain a better understanding of their experience in out-of-home care. The participants were 20 individuals, 11 females and 9 males that had been placed in out-of-home care in their childhood for six months or longer. They filled in six self-report instruments: The Depression, Anxiety and Stress Scales, the Cantril’s Ladder of Life, the Multi-item measure of adult Romantic Attachment, the Quality of Life Scale, the Connor-Davidson Resilience Scale, and the Rosenberg Self-Esteem Scale. After completing all the measures, the researcher asked the participants open-ended questions about their experiences of being removed from their homes and placed in out-of-home care. Framework Analysis was used to analyse the data. The results indicate that 14(70%) of the participants have low resilience, 14(70%) estimate that their quality of life is lower than average, 11(55%) have low self-esteem, and around 6(30%) meet the criteria for moderate (or higher) symptoms of depression, anxiety, and stress. One of most notable findings from the qualitative part of the study was that not a single participant felt that they were taken from their home too soon. Welfare services may consider providing long-term care for these vulnerable individuals